Analisis Etnofisika pada Proses Pembuatan dan Pengoperasian Alat Tenun Sesek di Desa Pringgasela - Baiq Aryani Novianti; Rena Dewi Pratiwi; Sopia Dwi Ariani; Khaerus Syahidi; Tsamarul Hizbi; Badrul Wajdi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to investigate the ethnophysics concepts embedded in the process of producing traditional Sesek woven fabric using the Gedogan loom in Pringgasela Village, East Lombok Regency. Traditional weaving represents a form of local wisdom that not only preserves cultural heritage but also embodies scientific principles that can be utilized as contextual learning resources in physics education. This research employed a qualitative descriptive approach within an ethnoscience perspective. Data were collected through direct observations of weaving activities, semi-structured interviews with experienced traditional weavers, and documentation of weaving processes and equipment. The collected data were analyzed through data reduction, data presentation, and conclusion drawing, supported by source and method triangulation to ensure data validity. The findings reveal that the weaving process reflects various physics concepts, particularly rigid body equilibrium, torque, tensile force, compressive force, rope tension, and mechanical motion. The Gedogan loom operates based on the principles of force and moment equilibrium, enabling stability throughout the weaving process. In addition, the body posture adopted by weavers demonstrates the application of biomechanical principles associated with rigid body equilibrium. The study also found that the materials used for each component of the loom are selected based on generations of empirical knowledge, resulting in mechanical properties appropriate for their respective functions. These findings indicate that the indigenous knowledge of the Pringgasela community has significant potential to serve as a culturally contextualized physics learning resource while simultaneously supporting the preservation of local cultural heritage